The peripheral and decidual immune cell profiles in women with recurrent pregnancy loss - Qin, Dengke; Xu, Huihui; Chen, Zechuan; Deng, Xujing; Jiang, Shan; Zhang, Xiaoming; Bao, Shihua (Frontiers in Immunology, 2022)
Recurrent pregnancy loss (RPL) affects 1-2% of couples of reproductive age. Immunological analysis of the immune status in RPL patients might contribute to the diagnosis and treatment of RPL. However, the exact immune cell composition in RPL patients is still unclear. Here, we used flow cytometry to investigate the immune cell profiles of peripheral blood and decidual tissue of women who experienced RPL. We divided peripheral immune cells into 14 major subgroups, and the percentages of T, NKT and B cells in peripheral blood were increased in RPL patients. The decidual immune cells were classified into 14 major subpopulations and the percentages of decidual T, NKT cells and CD11chi Mφ were increased, while those of CD56hi decidual NK cells and CD11clo Mφ were decreased in RPL patients. The spearmen correlation analysis showed that the proportion of peripheral and decidual immune cells did not show significant correlations with occurrences of previous miscarriages. By using flow cytometry, we depicted the global peripheral and decidual immune landscape in RPL patients. The abnormalities of peripheral and decidual immune cells may be involved in RPL, but the correlations with the number of previous miscarriages need further verification.